(untitled) (Revista Contexto & Educação, 2026)
The Climate Emergency (CE) requires profound changes in the relationship between society and the environment, based on scientific knowledge and guided by the principles of socio-environmental justice. In this sense, Environmental Education (EE) is a relevant alternative for promoting such changes, as it favors paradigm shifts, such as the reconnection between humans and nature. In schools, it is necessary to use methodologies that encourage students to take the lead in addressing CE and overcome existing disciplinary fragmentation. Thus, this article aims to identify and analyze the support tools used by elementary school teachers in teaching about CE. The research took place within the scope of a project that encouraged youth leadership, reflecting on the importance of pedagogical practice on CE. The results showed that teachers sought alternative materials to textbooks for teaching CE, using active methodologies supported by theoretical references. In addition, their occasional difficulties with the process demonstrated that there are weaknesses in teacher education, a fact that can hinder the practice of EE and, consequently, influence human actions to address this problem.